You are on page 1of 5

# Method 1: Finding an equation when

x=13 , x=5

x13=0 , x+5=0

## 2. Write down as the product of two factors

(x13) (x+5)=0

Notice that the signs in the brackets are opposite of the given roots.
3. Expand the brackets

x28x65=0

## Note that if each term in the equation is

multiplied by a constant then there could be
other possible equations which would have the same roots.
For example,

Multiply by 2: 2x216x130=0
Multiply by 3: 3x2+24x+195=0
Method 2: Sum & Products
of Roots are Given
Sum of Roots Product of Roots

= =

ax2+bx+c = 0

## Step 2: Then we write quadratic equation given

the sum and product of its roots.

x2- ( )x + = 0

or

x2 + sx + p = 0

## Where s = sum of roots

p = product of roots

Step 3: Take the given values and plug them into the
equation. Last one is to write the final answer.

x2 + sx + p = 0 sum of roots

product of roots
Examples in Method 1:

1. e=2 , e=2
e-2=0, e-2=0
(e-2)(e-2)=0
ex2-4e+4=0

2. r=5 , r=-2
r-5=0 , r+2=0
(r-5)(r+2)=0
r2-3r-10=0

3. i=-3 , i= -9
i+3=0 , i+9=0
(i+3)(i+9)=0
i2+12i=27=0

4. c=10 , c=35
c-10=0 , c-35=0
(c-10)(c-35)=0
c2-45c+350=0

5. a=6 , a=-8
a-6=0 , a+8=0
(a-6)(a+8)=0
a2+2a-48=0
Examples in Method 2

2+2=4 =4

=4 ax2+bx+c = 0

ex2-4e+4=0
= -4

3+4=7 = 12

=7 ax2+bx+c = 0

rx2-7r+12=0
= -7

2+5=7 = 14

=7 ax2+bx+c = 0

ix2-7i+14=0
= -7

## 4. c=-5 , c=-7 (-5)(-7) = 35

-5+(-7)=-12 = 35

= -12 ax2+bx+c = 0

= 12 cx2+12c+35=0

## 5. a=-10 , a=5 (-10)(5) = -50

-10+5=-5 = -50

= -5 ax2+bx+c = 0
ax2+5a-50=0

=5